Las ediciones digitales de la prensa: los columnistas y la interactividad con los lectores. - Edo, Concha (Estudios sobre el Mensaje Periodístico, 2000)
The widespread access to Internet and the increase of digital media communication seemed to put in danger the survival of the press as known up to now. Yet the evolution that is taken place in the technological environment is apparently not leading to such bad end but to coexistence of written press, radio, TV and the net for much longer than experts could forsee. With a close study of the context of the on-line press, it can be seen that the readers look more for information than for opinions and that columnists hardly arouse interest on screen. 63 Concha Edo Las ediciones digitales de la prensa: los columnistas y la interactividad con los lectores This is due to that minimun interaction that takes place with the readers and because of a desing too much alike "the papers". It´s still far away from the future multimedia.